O uso de critérios para avaliação de restaurações em dentes decíduos por alunos de graduação e pós-graduação impacta na decisão de tratamento? - Pedrotti, Djessica (2019)
This study aimed to evaluate the impact of the use of clinical criteria for the evaluation of restorations in primary teeth. For this, a convenience sample was used. Twenty-seven composite resin restorations of primary molars performed in 11 children who attended the Odontopediatric Clinic of the Federal University of Santa Maria were selected. Five undergraduate students and five graduate students were trained to evaluate the quality of restorations based on the criteria proposed by the World Dental Federation (FDI). Examiners independently performed the clinical evaluations of the restorations. Prior to the training of examiners, restorations were evaluated according to personal judgment to determine the need for intervention (repair or replacement). In case reintervention was needed, the reason was recorded. After 2 weeks, the same restorations were evaluated according to the FDI criteria. After all evaluations, two examiners with experience in assessing the restorations’ quality and using the FDI criteria examined the same restored teeth in children involved in the study. In consensus, they judged whether each restoration was clinically satisfactory or required repair or replacement. These results were considered the reference standard. For the analyses, two outcomes were considered: more or less invasive based on the FDI criteria in comparison with personal judgment. Poisson regression analysis was used to identify possible factors associated with outcomes. The numbers of true positive, true negative, false positive, and false negative results, according to the reference standard, were also recorded. Examiners that took more time to evaluate the restorations were more invasive based on the FDI criteria (rate ratio (RR)=1.00, 95% confidence interval (CI)=1.00–1.00; p=0.03). The mean time to evaluate restorations based on the FDI criteria was two times greater than for personal judgment. The students were more invasive with the use of the FDI criteria when examined children with greater caries experience (RR=1.16, 95% CI=1.01–1.32; p=0.03). Examiners were less invasive with FDI criteria when restorations involving multiple surfaces were evaluated (RR=2.04, 95% CI=1.03–4.05; p=0.04). The examiners' experience did not influence the clinical decision-making. A greater number of false positive results were observed when decision-making was more invasive based on the FDI criteria, while a greater number of false negative results were reported when students were less invasive based on the FDI criteria. Overall, the students tended to agree with the clinical evaluation of the restorations and subsequent treatment decision. In conclusion, the use of the criteria proposed by FDI had an impact on the evaluation of restorations’ quality and treatment decision. However, the level of examiner experience did not influence the decision-making.